Anisotropically tuning interfacial thermal conductance between graphite and poly(ethylene oxide) by lithium-ion intercalation: A molecular dynamics study. (October 2022) - Tian, Siyu; Xu, Zhihao; Wu, Shiwen; Luo, Tengfei; Xiong, Guoping
Highlights: Anisotropically enhanced thermal transport betw000een lithiated graphite and PEO. Strong LJ interaction between lithiated graphite and PEO contributes to high ITCs. The cross-plane ITC monotonically increases with increasing degree of lithiation. Significantly enhanced in-plane ITC is only observed in LiC6 /PEO system. Abstract: Understanding interfacial thermal transport between lithiated two-dimensional materials and polymers can provide useful guidelines to design thermally tunable and conductive composites for efficient thermal management of energy systems. In this work, molecular dynamics simulations are conducted to investigate the effect of lithium (Li)-ion intercalation on the interfacial thermal transport between graphite and poly(ethylene oxide) (PEO). Results show that Li-ion intercalation anisotropically affects the enhancement of the interfacial thermal conductance (ITC) between graphite and PEO. The cross-plane ITC monotonically increases with increasing degree of lithiation, while a significant enhancement of the in-plane ITC is only observed when the graphite host is fully lithiated. The anisotropic effect can be attributed to the intercalation-induced strong Lennard-Jones interactions between the two contacting materials. This work may open up new opportunities to design thermally conductive polymeric composites and thermally controllable interfaces through ion intercalation of 2D materials.